The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3897/zookeys.833.30689
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Neonrosella vitiata (Darwin) and Newmanella spinosus Chan & Cheang (Balanomorpha, Tetraclitidae) from the Andaman Sea, eastern Indian Ocean

Abstract: In this present study, distantly related acorn barnacle species in the subfamily Newmanellinae (Cirripedia, Thoracica, Tetraclitidae), including Neonrosellavitiata (Darwin, 1854) and Newmanellaspinosus Chan & Cheang, 2016, were discovered in the Andaman Sea of Thailand. Neo.vitiata can be readily distinguished from other newmanellids by shell plate and operculum morphology (external shell, tergum geometry, and pattern of parietal tube) and arthropodal characters (presence of basi-dorsal point at base o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Neonrosella vitiata was previously recorded from the Indo-west Pacific, Indian Ocean, Nicobar Island to Australia, Indonesia, Malay Archipelago, Sulu Archipelago, Philippines, and the Pacific Ocean (Jones and Hosie 2016). Recently, Neonrosella vitiata also was discovered in the Andaman Sea of Thailand (Sukparangsi et al 2019). In this study, N. vitiata was found on Ambon Island (at Liang), Banda Island and Saparua Island (at Tuhaha) on port poles, reef and stones (a map with the occurrence of Neonrosella vitiata in the Moluccas is shown in Suppl.…”
Section: Genbank Accession Number 18s (Mk981384)mentioning
confidence: 52%
“…Neonrosella vitiata was previously recorded from the Indo-west Pacific, Indian Ocean, Nicobar Island to Australia, Indonesia, Malay Archipelago, Sulu Archipelago, Philippines, and the Pacific Ocean (Jones and Hosie 2016). Recently, Neonrosella vitiata also was discovered in the Andaman Sea of Thailand (Sukparangsi et al 2019). In this study, N. vitiata was found on Ambon Island (at Liang), Banda Island and Saparua Island (at Tuhaha) on port poles, reef and stones (a map with the occurrence of Neonrosella vitiata in the Moluccas is shown in Suppl.…”
Section: Genbank Accession Number 18s (Mk981384)mentioning
confidence: 52%
“…The distribution of intertidal barnacles is different between the coastline in the Gulf of Thailand and the Andaman Sea (Pochai et al 2017): the Andaman side has a higher species diversity (nine total species in Andaman side and six in the Gulf of Thailand). Octomeris was not reported by Pochai et al (2017) or Sukparangsi et al (2019). The record of O. intermedia in the present study brings the number of Thai intertidal barnacle species to 12.…”
Section: Discussionmentioning
confidence: 40%
“…Intertidal barnacle diversity in Thailand received very little attention until the recent studies of Pochai et al (2017) and Sukparangsi et al (2019), who conducted detailed surveys of Thai intertidal barnacles and recorded a total of eleven species from the Thai coastline. The distribution of intertidal barnacles is different between the coastline in the Gulf of Thailand and the Andaman Sea (Pochai et al 2017): the Andaman side has a higher species diversity (nine total species in Andaman side and six in the Gulf of Thailand).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many marine species that have genetically homogeneous population across these two ecoregions, probably due to high dispersal abilities following the glaciations (e.g., the trumpetfish Aulostomus chinensis, Bowen et al, 2001;sea urchin Tripneustes, Lessios et al, 2003, gastropod Echinolittorina reticulata, Reid et al, 2006, seaweed Sargassum, Chan et al, 2013, 2014. Pochai et al (2017) and Sukparangsi et al (2019) surveyed the diversity of barnacles in Thailand and revealed that the species composition of barnacles is different between the Gulf of Thailand and Andaman Coral Sea ecoregions. This suggest that species diversity in these two ecoregions can be affected by present-day oceanographic currents or geological events.…”
Section: Introductionmentioning
confidence: 99%